Estrategias de marketing en la Empresa Avícola Keven de el Cantón Vinces de la provincia de Los Ríos en el periodo 2023. - Santana Loor, Adrián Agustín (2024)
This study focuses on the Avícola Keven company, located in the Vinces Canton, Los Ríos Province, Ecuador. The company, which is dedicated to the sale of birds, faces significant challenges due to the lack of efficient marketing strategies. The objective of the study is to analyze and improve these strategies to increase the competitiveness and marketing of their products. Businesses in Vinces, particularly small ones, have difficulty increasing their sales due to their limited knowledge of marketing strategies. This lack of knowledge negatively affects the marketing of their products. Furthermore, lack of technological and marketing skills among local entrepreneurs prevents proper promotion, reducing their market reach. The research is justified by the need to improve the marketing of poultry products in Vinces. The implementation of marketing strategies will allow local producers to promote their products more effectively, taking advantage of digital platforms to reach a wider audience and build customer loyalty. That is why we seek to analyze the marketing strategies in the Keven Poultry company of the Vinces Canton. Qualitative and quantitative methods were used to collect data through surveys carried out on a representative sample of the population of the Vinces Canton.